(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2022)
OID is an homage to Darío Santillán and Maximiliano Kosteki by Argentinian composer Juan Pampin (b. 1967). The piece, scored for piano, live electronics, and video consists of a set of variations on the introduction of the piano version of the Argentinian National Anthem, which, according to the composer, ciphers the Argentinian catastrophic destiny. Not ignoring the composer’s ideas on his piece, we propose that OID offers a singular –musical– perspective of post-2001Argentina. This means that the music is not (just) the testimony of a ‘disaster’, but it also opens a crack which allows for the emergency of a new perspective, an emancipatory power to aid us in rethinking the present and the future. To go through this aesthetic political operation, we analyze Pampin’s piece by looking for moments where compositional technique and aesthetic discourse intersect. To do this, we follow Theodor Adorno’s critique of Gustav Mahler, which gives us clues to understand the destructive-constructive process that of this work. It is not about reconciling our broken national identity, but to embrace this fracture, its deformity, and to amplify it, thus providing a way to allow the defeated to speak up.